Efficacy of Intravenous Immunoglobulin for Systemic Manifestations of Dermatomyositis Beyond Muscular and Cutaneous: Sub-analysis of the ProDERM Study - Aggarwal, Rohit; Schessl, Joachim; Bata-Csörgő, Zsuzsanna; Dimachkie, Mazen M; Griger, Zoltan; Moiseev, Sergey; Oddis, Chester V; Schiopu, Elena; Vencovský, Jiri; Clodi, Elisabeth; Levine, Todd; Charles-Schoeman, Christina; et al. (Rheumatology and therapy, 2025)
INTRODUCTION: Muscle and skin involvement are well defined in dermatomyositis but other symptoms contribute significantly to the disease burden and their treatment is not well characterized. This post hoc analysis of ProDERM assessed the effect of intravenous immunoglobulin (IVIg) treatment on other manifestations of dermatomyositis beyond muscular and cutaneous involvement. METHODS: ProDERM was a randomized, placebo-controlled study. For weeks 0-16, patients with dermatomyositis received 2.0 g/kg IVIg (Octagam, 10%) or placebo every 4 weeks. Eligible patients entered the open-label extension, where all received IVIg to week 40. Pulmonary, skeletal, constitutional, gastrointestinal, and cardiovascular disease activity was assessed using the myositis disease activity assessment tool, comprising a visual analog scale (VAS; 0-10 cm) and myositis intention-to-treat activity index. RESULTS: Of 95 patients enrolled, 47 received IVIg and 48 received placebo to week 16. At baseline, 37.9% of patients experienced pulmonary, 64.2% experienced skeletal, 76.8% experienced constitutional, 33.7% experienced gastrointestinal, and 15.8% experienced cardiovascular involvement (VAS > 0.5). Among these patients, for those on IVIg, the following mean VAS scores decreased from baseline to week 16: pulmonary (37.7%; P = 0.001), skeletal (52.6%; P < 0.001), constitutional (44.4%; P < 0.001), and gastrointestinal (49.2%; P = 0.005). No corresponding improvement was seen with placebo except for constitutional VAS. With IVIg, the proportions of patients with arthritis (36.2 to 17.8%; P = 0.01), arthralgia (68.1 to 0.0%; P < 0.001), and fatigue (68.1 to 3.3%; P = 0.008) decreased from baseline to week 16. In the combined cohort, the proportions of patients with dysphonia (20.0 to 8.1%; P = 0.04), arthralgia (66.3 to 39.8%; P < 0.001), weight loss (10.5 to 3.4%; P = 0.04), fatigue (75.8 to 50.0%; P < 0.001), and dysphagia (40.0 to 18.4%; P < 0.001) decreased from baseline to week 40. CONCLUSION: IVIg was effective in treating pulmonary, skeletal, constitutional, and gastrointestinal manifestations of dermatomyositis. We advocate exploring IVIg as treatment for dermatomyositis, beyond muscle and skin manifestations. TRIAL REGISTRATION: ClinicalTrials. gov identifier, NCT02728752.
Keywords: Pulmonary; Octagam; Skeletal; Constitutional; Gastrointestinal; Arthritis; Dermatomyositis; Intravenous; Immunoglobulins; Arthralgia